An adventure in statistics : the reality enigma - Field, Andy P., 1973- (Thousand Oaks (Calif.) : Sage, 2016)
Andy Field's unique approach introduces students across the social sciences to the importance and relevance of statistics in a lavishly illustrated format and style that overcomes traditional anxiety for the subject and dullness of typical offerings. As with the immensely successful Discovering Statistics Using IBM SPSS Statistics and Discovering Statistics Using R,his motives for writing Discovering Statistics: The Reality Enigma stem from his desire to make statistics a bit more pleasant to learn and to counter his negative experience of textbooks when he was a student. The medium, the message and the rock-solid statistics coverage combine to raise the level of attainment of even the most Maths-phobic student on their first statistics course, covering in more detail, the introductory content his previous books touch on. In doing so, it provides an unrivalled launchpad to further study, research and inquisitiveness about the real world which equips students with the skills to succeed in their chosen degree and which they can apply in the workplace.